The Potential of Populus deltoides in the Sub-humid Tropics of Central India : Survival, Growth and Productivity - Puri, Sunil; Swamy, S. L.; Jaiswal, A. K. (Indian Forester, 2001)
The study describes growth, biomass and net primary productivity in different clones of Populus deltoides Bartr. Grown on vertisol type of soil at Raipur situated at 21Â°12’N latitude and 81Â°36Â°E longitude. Based on growth and survival performance of 106 clones in the nursery over successive two years, 19 clones were selected for field evaluation. Survival in the field in different clones ranged from 40 to 100 per cent. The best five clones in 4 yr old plantation was in order of 65/27 > S7Cl > G48 > G3 > D121. The above- ground biomass varied from 2.79 to 43.77 MT ha-1, while that of coarse roots it was 0.67 to 10.5 Mg ha-1. Stem wood in different clones varied from 33.7 to 62.2 per cent of the total biomass followed by coarse roots (16.5-28.0%), branches (7.4-23.7%), bark (7.5-12.9%) and leaves (5.3-10.3%). Net primary productivity also differed in different clones. The study concludes that some of the clones can be grown at 21Â°N latitude which was to date not considered a suitable region for the introduction of P. deltoides.